2023
DOI: 10.1021/acsapm.2c02041
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible Gels of Poly(l-lactide)/Poly(d-lactide) Blends: A Facile Route to Prepare Blend α-Form and Stereocomplex Aerogels

Abstract: The demand for biodegradable polymer-based aerogels with superior comprehensive properties has escalated in various fields of application, such as packaging, tissue engineering, thermal insulation, acoustic insulation, and environmental remediation. In this work, we report a facile strategy for enhancing the thermal and mechanical properties of polylactide (PLA) aerogels through the stereocomplex (SC) formation between the opposite enantiomers. Thermoreversible gelation of poly(L-lactide) (PLLA)/poly(D-lactide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…The PMX aerogels show strong mechanical properties: for example, the PMX-30 aerogel can bear a metal block, which is 2000 times heavier than that of the aerogel (Figure c) without any deformation. These results suggested that the hybrid aerogels have a better compressive performance than the pristine PVDF aerogel, and all of them showed an irreversible buckling behavior similar to that of most of the semicrystalline aerogels. , It is also to be noted that the compressive strength values of the PMX hybrid aerogels are significantly higher than those of the MXene aerogels because of the strong noncovalent interactions between PVDF chains and the surface functionalities of MXene nanosheets. , …”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The PMX aerogels show strong mechanical properties: for example, the PMX-30 aerogel can bear a metal block, which is 2000 times heavier than that of the aerogel (Figure c) without any deformation. These results suggested that the hybrid aerogels have a better compressive performance than the pristine PVDF aerogel, and all of them showed an irreversible buckling behavior similar to that of most of the semicrystalline aerogels. , It is also to be noted that the compressive strength values of the PMX hybrid aerogels are significantly higher than those of the MXene aerogels because of the strong noncovalent interactions between PVDF chains and the surface functionalities of MXene nanosheets. , …”
Section: Resultsmentioning
confidence: 85%
“…These results suggested that the hybrid aerogels have a better compressive performance than the pristine PVDF aerogel, and all of them showed an irreversible buckling behavior similar to that of most of the semicrystalline aerogels. 6,58 It is also to be noted that the compressive strength values of the PMX hybrid aerogels are significantly higher than those of the MXene aerogels because of the strong noncovalent interactions between PVDF chains and the surface functionalities of MXene nanosheets. 20,28 Other indispensable requirements for the applications of these aerogels in harsh environments are thermal stability and flame retardancy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…PLLA is known to form gels in particular solvents that favor the formation of co-crystals or crystalline complexes (e form). 30,[69][70][71] Fig. 8(a) shows the digital photograph of curcumin-PLLA gel in DMF under UV light along with the POM image.…”
Section: Resultsmentioning
confidence: 99%
“…Physical aerogels are one subsection of polymeric aerogels which differ from covalent aerogels in that their network connectivity is derived from non-permanent and often thermally labile junctions, which constitute a physically crosslinked network . Several semicrystalline polymers that are devoid of hydrogen-bonding groups or ionic functionalities have been shown to form aerogels, with polymer crystallites and chain entanglements acting as the physical crosslinks within the open microstructure. Recent examples of crystallizable polymers that have been shown to form physical aerogels include syndiotactic polystyrene, isotactic polypropylene, poly­(phenylene oxide), poly­(vinylidene fluoride), poly­( l -lactide) and poly­( l -lactide)/poly­( d -lactide) blends, , and poly­(ether ether ketone). Current applications of physical polymeric aerogels include three-dimensional separation membranes, airborne nanoparticle filters, catalysis supports, thermal insulation, and gel-state platforms for blocky copolymer functionalization. Expanding the applicability of physical aerogels necessitates the transition to high-performance polymers.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several semicrystalline polymers that are devoid of hydrogen-bonding groups or ionic functionalities have been shown to form aerogels, with polymer crystallites and chain entanglements acting as the physical crosslinks within the open microstructure. 9−17 Recent examples of crystallizable polymers that have been shown to form physical aerogels include syndiotactic polystyrene, 9 isotactic polypropylene, 10 poly-(phenylene oxide), 11 poly(vinylidene fluoride), 12 poly(L-lactide) and poly(L-lactide)/poly(D-lactide) blends, 13,14 and poly-(ether ether ketone). 15−17 Current applications of physical polymeric aerogels include three-dimensional separation membranes, 12 airborne nanoparticle filters, 18 catalysis supports, 19 thermal insulation, 20 and gel-state platforms for blocky copolymer functionalization.…”
Section: ■ Introductionmentioning
confidence: 99%